(untitled) (PANGEEA, 2025)
Qatar between geographical and geopolitical extremes. Among the world’s states, big and strong, developed and in development and between the small, usually with limited potential, there are a number of atypical states that are generally small in size, but it’s coming out in the geographic and geopolitical issues. One of these, which has defied the hostile nature and time, and came to the attention of the world with plenty of extreme geopolitical and geographical is the small State of Qatar, the Arab World, situated on a huge sponge for oil and natural gas, huge luck that has influenced the evolution and today’s image of the country.